Perbedaan Pengaruh Latihan Metode Drill Passing Atas dan Passing Atas Berpasangan Terhadap Kemampuan Passing Atas Dalam Permainan Bola Voli pada Tim Bola Voli Putra SMP Muhammadiyah 5 Ngawi - Fahima, Al Rizal Zam Zam; Irfan, Mohammad; Darumoyo, Kuncoro (Civiliza Publishing, Indonesia., 2023)
The purpose of this study was to determine the results of the differences in the influence of the upper passing drill and paired upper passing training methods on the upper passing ability in volleyball games on the SMP Muhammadiyah 5 Ngawi men's volleyball team. And to find out which training has a better effect between the upper passing drill and paired upper passing training methods on the upper passing ability in volleyball games on the SMP Muhammadiyah 5 Ngawi men's volleyball team. This study was conducted on the volleyball court of SMP Muhammadiyah 5 Ngawi with an experimental method, involving 30 athletes who were divided into two groups to compare the results of upper passing training using two different methods. The results showed that there was a significant difference between the upper passing drill and paired upper passing training methods on the upper passing ability in volleyball games on the SMP Muhammadiyah 5 Ngawi men's volleyball team, with the upper passing drill method having a better effect. This is evidenced by the t count which is greater than the t table at a significance level of 5%. The percentage increase in upper passing ability was also higher in the group that underwent training with the upper passing drill method (23.45%) compared to the paired upper passing training group (22.90%). Drill, Drill Passing Method, Volleyball Game.